(untitled) (Revista Română de filosofie analitică, 2024)
A law saying that heavier bodies fall faster than lighter ones has been held to be refutable independently of empirical experiments, with a priori “thought experiments”. I argue that these thought experiments do not qualify as good arguments against the law.